NEED ASSESSMENT PENGGUNA TERHADAP LULUSAN BKI DAN APLIKASINYA DALAM PENYELENGGARAAN JURUSAN - Afnibar Afnibar (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Increasing the number of students is the hope of all educational institutions, because it is one measure of quality improvement organizations. It can even affect the accreditation of the majors, so that the various promotions must be performed. The consequences are an increasing number of students to be offset by an increase in services by the department, faculty and institute. It is the responsibility of the agency to improve the education and learning process. Implementation of the learning process by making use of learning technologies, through the development. Improved services that is performed by faculties and institutes concerned with academic and non academic services. Academically, through giving scholarships and training as well as complementary facilities and infrastructure. In non-academic, it is held various competitions and other students’ activities (such as scouts, student regiment, PMI, Islamic study groups, Mapala, theater, music and voice of campus). Other efforts are undertaken to assess and cooperate with the users about the performance of graduates in the field continuously. In particular majors Counseling Islam has collaborated with various institutions, namely: the Ministry of Justice and Human Rights, Ministry of Religious Affairs Level I and the city of Padang, Siti Rahmah Hospital, Yarsi Ibn Sina Hospital, Aisyiah Hospital, and Dr. M. Jamil Hospital and other related agencies. Need assessment gives an honest description about the management of an institution